THE RELATIONSHIP BETWEEN KNOWLEDGE AND FAMILY SUPPORT WITH ANXIETY IN PREMENOPAUSAL WOMEN AT PEKIK NYARING COMMUNITY HEALTH CENTRE CARE, CENTRAL BENGKULU REGENCY 2022 - Elly Wahyuni; Mariati Mariati; Lela Hartini; Dwie Yunita Baska; Mariana Tantiri Mariana Nainggolan (Proceeding B-ICON, 2022)
The percentage of the incidence of anxiety experienced by premenopausal women worldwide is still relatively high (77%). About 25% of anxiety occurs during menopause, with various symptoms caused by individuals, depending on psychological and emotional. This study aimed to determine the relationship between knowledge and family support with anxiety incidence in premenopausal women at the Pekik Nyaring Community Health Centre, Central Bengkulu Regency, in 2022. The research design used a cross-sectional approach. The population in this study were all women aged 45-55 years in 12 Integrated Post for Non-Communicable Diseases or Pos Pelayanan Terpadu Penyakit Tidak Menular (Posbindu PTM ) Pekik Nyaring Community Health Centre, totalling 981 people. The sample in this study was 78 respondents taken by purposive sampling, and the number of samples distributed in each Posbindu was not equal. Data analysis using univariate and bivariate analysis using Chi-Square. The results showed that 78 premenopausal women (53.8%) experienced moderate and severe anxiety, (59%) had poor knowledge, and (65.4%) had poor family support. There was a relationship between knowledge and anxiety in premenopausal women with p=0.002 < 0.05 and OR = 5.0. It means that premenopausal women with poor knowledge were 5 times more likely to experience moderate and severe anxiety. There was a relationship between family support and premenopausal women's anxiety, p=0.000 < 0.05 and OR = 8.4. It means that premenopausal women who receive family support were at least 8 times more likely to experience moderate and severe anxiety. Suggestions for the Community Health Centre, in this case, the Head of the Community Health Centre, can optimise health workers to create innovative programs related to women's preparation for menopause